Aspek Hukum Peralihan Hak Milik Tanah Karena Hibah - Qasthary, Auzan; Suhaibah; Abdullah, Fathin (Sagita Academia Journal, 2025)
The transfer of inherited assets is only for people who have rights and obligations over the assets. It will be different when a couple or family is destined not to be able to have children and they adopt a child, then the transfer of inheritance can be done by means of a gift or mandatory will. Gifts can be in any form, one of which is donating land to an adopted child. The aim of this research is to determine the legal aspects of the transfer of land ownership rights due to a grant in Gampong Sagoe, Glumpang Baro District. This research is a type of empirical juridical research, namely field research by collecting data through secondary data by studying related books, journals and scientific works and for primary data by interviewing respondents and informants. The results of this research show that the legal aspect of the transfer of land ownership rights due to a grant in Gampong Sagoe, Glumpang Baro District is by checking the authenticity of the land certificate by PPAT. The PPAT in charge is obliged to request important documents that must be provided by the grantor and potential grantee, such as data relating to the land and personal identity of each party. Once the required documents are complete, the Notary/PPAT can execute the land grant contract, and the parties agree on the agreement and the PPAT signs the grant deed and the grant deed that has been issued by the PPAT must be registered at the Land Office. Advice, it is hoped that the public will understand and study more deeply about religious knowledge and the rules regarding grants in the Compilation of Islamic Law, so that undesirable things do not happen to givers and recipients of grants.